Manajemen dan Strategi Dakwah Pengajian Ikatan Sosial Kerukunan Air Sengak Rejang Lebong - Murniyanto Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of this study was to determine the management and da'wah strategy of the ISK Air Sengak Rejang Lebong study. The method is by interviewing the leader of the recitation of the ISK Air Sengak Rejang Lebong recitation, using the library, the author using a reference book,documents accompanied by monthly recitation reports to strengthen the data. The results obtained by the author of Islamic preaching are: (a) applying the teachings of tauhid in the content of da'wah, (b) applying to the community about the teachings of Islam so that people understand the teachings of Islam and want to implement them and practice them so that there are changes in daily life (c) applying imprative da'wah to members of social ties, water harmony is carried out in monthly recitation of ISK mingling with the community and other Muslims, especially on Rt.7,8 and 9 Rw.3 Air Sengak Rejang Lebong, (d) Overall management function as planning.So that what is done by members of the ISK orsos can be aimed at a good path.